Exploring staff experiences: A case for redesigning the response to aggression and violence in the emergency department. (July 2021) - Davids, Jennifer; Murphy, Margaret; Moore, Nathan; Wand, Timothy; Brown, Martin
Highlights: The bulk of cases fell into three categories of disease: mental illness, dementia and drugs and alcohol. The main trigger cited for the aggression and violence was waiting times exacerbated by fear, anxiety and a sense of not knowing. There is an ongoing culture of under-reporting and acceptance of abuse which impacts on staff emotionally, psychologically and physically. At the time of being interviewed, nearly a third of staff had not received formal violence prevention training and staff were unclear about when exactly to activate violence intervention. The response to aggression and violence in the ED lacks methodical coordination of resources and personnel and there is an urgent need to redesign the staff response to and training for aggression and violence in the ED. Abstract: Introduction: A Code Black is the coordinated response by healthcare staff and security to an act or threat of verbal and physical aggression or violence perpetrated by a patient, family member or visitor towards healthcare staff within a hospital setting. Behavioural disturbance is often verbally de-escalated by staff. However, as a last resort physical and/or chemical restraint may be necessary. Reports show that there is an increasing number of violent incidents in Emergency Departments (ED), emphasising the importance of staff training for Code Black events. This research examines the response of healthcare staff to aggression and violence in the ED, the supporting structures that manage a Code Black event and potential avenues for restructuring the response. Methods: We used a constructivist methodology to evaluate the training needs of healthcare staff. In 2019, we interviewed 20 staff and conducted a series of ethnographic observations in EDs across four hospitals in the Western Sydney Local Health District (WSLHD) in New South Wales (NSW), Australia. We focussed on staff experiences of Code Black events and the current departmental response. Staff recounted experiences of 45 Code Black events which were collated and thematically analysed. Results: Our findings show that there are no guidelines for: assessing the risk of an agitated patient, best practice de-escalation techniques, when exactly to call a Code Black and the pre-determined allocation of staff roles for patient restraint. Code Black response efforts lacked a systematic approach to coordinating resources and personnel, and there was confusion over the role of security. When poorly managed, this placed healthcare staff, security personnel and patients at serious risk and had a negative impact on staff wellbeing. We found training in Code Black interventions relies heavily on learning on the job from experienced staff members. Conclusion: A systematic, coordinated and consistent organisational response to Code Black events is essential for the safety of ED staff. The roles and responsibilities of health workers and security require clear definition, and health workers across the WSLHD require easily accessible and repeatable experiential training in managing Code Black events.